At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's solve the problem step by step by expanding the given binomial expression [tex]\((x^{3n} + y^{3m})^3\)[/tex].
To expand [tex]\((a + b)^3\)[/tex], we use the binomial theorem, which is written as follows:
[tex]\[ (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3 \][/tex]
In our case, we let:
[tex]\[ a = x^{3n} \quad \text{and} \quad b = y^{3m} \][/tex]
Substituting these into our binomial expansion formula, we get:
[tex]\[ (x^{3n} + y^{3m})^3 = (x^{3n})^3 + 3(x^{3n})^2(y^{3m}) + 3(x^{3n})(y^{3m})^2 + (y^{3m})^3 \][/tex]
Now we need to simplify each term individually:
1. For [tex]\((x^{3n})^3\)[/tex]:
[tex]\[ (x^{3n})^3 = x^{3n \cdot 3} = x^{9n} \][/tex]
2. For [tex]\(3(x^{3n})^2(y^{3m})\)[/tex]:
[tex]\[ 3(x^{3n})^2(y^{3m}) = 3(x^{3n \cdot 2})(y^{3m}) = 3(x^{6n})(y^{3m}) = 3x^{6n}y^{3m} \][/tex]
3. For [tex]\(3(x^{3n})(y^{3m})^2\)[/tex]:
[tex]\[ 3(x^{3n})(y^{3m})^2 = 3(x^{3n})(y^{3m \cdot 2}) = 3(x^{3n})(y^{6m}) = 3x^{3n}y^{6m} \][/tex]
4. For [tex]\((y^{3m})^3\)[/tex]:
[tex]\[ (y^{3m})^3 = y^{3m \cdot 3} = y^{9m} \][/tex]
Combining all these terms together, we get:
[tex]\[ (x^{3n} + y^{3m})^3 = x^{9n} + 3x^{6n}y^{3m} + 3x^{3n}y^{6m} + y^{9m} \][/tex]
So, the expanded form of [tex]\(\left(x^{3n} + y^{3m}\right)^3\)[/tex] is:
[tex]\[ x^{9n} + 3x^{6n}y^{3m} + 3x^{3n}y^{6m} + y^{9m} \][/tex]
To expand [tex]\((a + b)^3\)[/tex], we use the binomial theorem, which is written as follows:
[tex]\[ (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3 \][/tex]
In our case, we let:
[tex]\[ a = x^{3n} \quad \text{and} \quad b = y^{3m} \][/tex]
Substituting these into our binomial expansion formula, we get:
[tex]\[ (x^{3n} + y^{3m})^3 = (x^{3n})^3 + 3(x^{3n})^2(y^{3m}) + 3(x^{3n})(y^{3m})^2 + (y^{3m})^3 \][/tex]
Now we need to simplify each term individually:
1. For [tex]\((x^{3n})^3\)[/tex]:
[tex]\[ (x^{3n})^3 = x^{3n \cdot 3} = x^{9n} \][/tex]
2. For [tex]\(3(x^{3n})^2(y^{3m})\)[/tex]:
[tex]\[ 3(x^{3n})^2(y^{3m}) = 3(x^{3n \cdot 2})(y^{3m}) = 3(x^{6n})(y^{3m}) = 3x^{6n}y^{3m} \][/tex]
3. For [tex]\(3(x^{3n})(y^{3m})^2\)[/tex]:
[tex]\[ 3(x^{3n})(y^{3m})^2 = 3(x^{3n})(y^{3m \cdot 2}) = 3(x^{3n})(y^{6m}) = 3x^{3n}y^{6m} \][/tex]
4. For [tex]\((y^{3m})^3\)[/tex]:
[tex]\[ (y^{3m})^3 = y^{3m \cdot 3} = y^{9m} \][/tex]
Combining all these terms together, we get:
[tex]\[ (x^{3n} + y^{3m})^3 = x^{9n} + 3x^{6n}y^{3m} + 3x^{3n}y^{6m} + y^{9m} \][/tex]
So, the expanded form of [tex]\(\left(x^{3n} + y^{3m}\right)^3\)[/tex] is:
[tex]\[ x^{9n} + 3x^{6n}y^{3m} + 3x^{3n}y^{6m} + y^{9m} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.